مناهج مقترحة لتعليم التعبيرات الاصطلاحية للناطقين بغير العربية - Yousuf, Mohamed Abdel Rahman Ibrahim (International Islamic University Malaysia (IIUM), 2011)
The paper discusses about three perceptions on the teaching methods of idioms to the non-native Arabic speakers. The problem statement is to recognize the suitable educational and linguistic frameworks to teach this particular topic. The main hypothesis is that teaching idioms cannot be neglected by the syllabus designers for teaching Arabic as a second language. To investigate this, the researcher had utilized the deductive and conclusive methods. Among the most important conclusions of the investigation are: there is a need to approach the teaching of idioms through three eventual levels which begins with the expressions from multiple choices, to be followed by the semantic fields and finally the comprehensive method.